Preparation method of lithium iron manganese phosphate positive electrode material, positive electrode material and lithium ion battery

Through the synergistic method of sand grinding, spray drying and three-stage sintering, the problem of low conductivity and low compaction density of lithium iron manganese phosphate cathode material is solved, high conductivity and high compaction density are achieved, and the electrochemistry is improved. performance.

CN119330323APending Publication Date: 2025-01-21JINGMEN GEM NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202411457343.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The preparation of lithium manganese iron phosphate positive electrode material has problems such as low conductivity, low compaction density and uneven mixing of Fe/Mn at the atomic level, resulting in poor electrochemical performance.

Method used

Adopt the synergistic method of sand grinding, spray drying, and three -stage sintering, grind the front -drive D50 to ultra -small particle size through sand grinding, spray dry and three -stage sintering to reduce the internal resistance of the material, improve the conductivity, and realize the element of elements Uniform distribution, improve the density of compaction.

Benefits of technology

It achieves high conductivity and high compaction density of lithium iron manganese phosphate cathode material, improving its electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330323A_ABST
    Figure CN119330323A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a lithium iron manganese phosphate positive electrode material, the positive electrode material and a lithium ion battery. The preparation method comprises the following steps: (1) sanding first slurry to obtain second slurry; and (2) carrying out spray drying and three-stage sintering on the second slurry to obtain the lithium iron manganese phosphate positive electrode material, the first slurry comprises a lithium source, a manganese source, an iron source, a phosphorus source and a solvent. According to the preparation method provided by the invention, the lithium manganese iron phosphate positive electrode material with wide distribution of large and small particles, high conductivity and high compaction density is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a preparation method of a lithium iron manganese phosphate positive electrode material, a positive electrode material and a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of long service life and environmental friendliness, and have been widely used in portable electronic devices and new energy vehicles. Among them, the positive electrode material largely determines the electrochemical properties, safety performance and manufacturing cost of lithium-ion batteries.

[0003] The olivine-type positive electrode material lithium iron phosphate has the advantages of low price and high safety, and has become one of the positive electrode materials for lithium-ion batteries for large-scale commercial applications. Another olivine-type positive electrode material lithium manganese iron phosphate has a higher voltage platform and energy density than lithium iron phosphate, and is therefore considered to be an upgraded version of lithium iron phosphate.

[0004] At present, the main problems in the preparation of lithium iron manganese phosphate positive electrode materials include low conductivity, low compaction density, and uneven micro-mixing of manganese and iron. To address the above problems, the existing technology adopts methods such as element doping and coating, reducing particle size, and improving crystallinity. For example, CN110323434A discloses a method for preparing a lithium iron manganese phosphate-carbon composite material and a lithium iron manganese phosphate-carbon composite material. First, a soluble manganese-containing phosphate, an organic iron salt, a manganese salt, and a lithium salt are dissolved in deionized water according to the element molar ratio to obtain a precursor solution, which is dried and granulated to obtain a lithium iron manganese phosphate precursor powder; the precursor powder is sintered under a protective atmosphere to obtain a sintered material, which is crushed and refined, and vacuum packaged to obtain a lithium iron manganese phosphate-carbon composite material. CN106486668A discloses a modified lithium iron manganese phosphate material, a preparation method and application thereof, which includes a magnesium-doped lithium iron manganese phosphate core layer and a boron-containing coating layer coated on the surface of the magnesium-doped lithium iron manganese phosphate core layer, a manganese source, a phosphorus source, an iron source, a lithium source, a magnesium source and water are mixed to form an intermediate reaction liquid; the intermediate reaction liquid is sequentially dried and pre-calcined to obtain a core layer precursor; the core layer precursor is mixed with a boron source and then roasted to obtain a modified lithium iron manganese phosphate material. However, in the preparation process of the above-mentioned precursor material and the positive electrode material, agglomeration of microscopic materials is easily generated, resulting in uneven mixing of Fe / Mn at the atomic level, and poor electrochemical performance of the material. The above-mentioned method cannot effectively solve the key problems of the lithium iron manganese phosphate material.

[0005] Therefore, it is urgently needed to improve the compaction density and conductivity of lithium manganese iron phosphate positive electrode materials and enhance their electrochemical performance. Summary of the invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing a lithium iron manganese phosphate positive electrode material, a positive electrode material and a lithium ion battery. The preparation method provided by the present invention obtains a lithium iron manganese phosphate positive electrode material with a wide distribution of particle sizes, high conductivity and high compaction density.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:

[0009] (1) sand-milling the first slurry to obtain a second slurry;

[0010] (2) spray drying the second slurry and performing three-stage sintering to obtain the lithium manganese iron phosphate positive electrode material;

[0011] The first slurry includes a lithium source, a manganese source, an iron source, a phosphorus source and a solvent.

[0012] The preparation method provided by the present invention cooperates with sand milling, spray drying and three-stage sintering, grinds the precursor D50 to an ultra-small particle size by sand milling, and undergoes subsequent spray drying and three-stage sintering, thereby greatly reducing the internal resistance of the material and improving the electrical conductivity of the material. At the same time, the uniform distribution of elements in the precursor material is achieved, and the compaction density of the lithium iron manganese phosphate positive electrode material is improved, so that the lithium iron manganese phosphate positive electrode material with a wide distribution of large and small particles, high electrical conductivity and high compaction density is obtained.

[0013] In the present invention, sand milling, spray drying and three-stage sintering must be coordinated to achieve the simultaneous improvement of compaction density and electrical conductivity. Without any one of the conditions, the joint improvement of compaction density and electrical conductivity cannot be achieved.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] Preferably, the solid content of the first slurry is 20-45%, for example 20%, 25%, 30%, 35%, 40% or 45%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] Preferably, the first slurry also includes a carbon source.

[0017] In the present invention, a carbon source is added to the first slurry, and after sand milling and spray drying, the carbon source is evenly distributed inside and on the surface of the precursor, and then a three-stage sintering is performed to obtain a uniformly distributed conductive carbon network, which further improves the conductivity of the lithium manganese iron phosphate positive electrode material; and the present invention does not limit the specific material type of the carbon source, and the present invention is applicable to any type of carbon source that can be used for liquid phase carbon coating. For example, the carbon source includes an organic carbon source or an inorganic carbon source, and the organic carbon source includes but is not limited to sucrose, glucose, fructose, lactose, starch, citric acid, tannic acid, polyvinyl chloride (PVC), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinyl pyrrolidone (PVP), polyacrylonitrile (PAN) or at least one of phenolic resin, and the inorganic carbon source includes but is not limited to acetylene black, graphite, conductive carbon black (Super-P) or carbon nanotubes, etc.

[0018] Preferably, based on the total mass of the lithium source, manganese source, iron source and phosphorus source as 100wt%, the added amount of the carbon source is 1 to 4wt%, for example, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt% or 4wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the rotation speed of the sand grinding treatment in step (1) is 1500-3000 rpm, for example, 1500 rpm, 1800 rpm, 2000 rpm, 2300 rpm, 2500 rpm, 2800 rpm or 3000 rpm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] Preferably, the D50 of the solid particles in the second slurry is 120 to 300 nm, for example, 120 nm, 125 nm, 130 nm, 135 nm, 140 nm, 145 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm or 300 nm, and preferably 120 to 150 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In the present invention, the D50 of the solid particles (i.e., the precursor material) in the second slurry is regulated by sand milling to 120-300 nn, which is beneficial to reducing the internal resistance of the material during the three-stage sintering process, thereby improving the electrical conductivity of the material, and is also beneficial to improving the compaction density; further regulating to 120-150 nm can better improve the compaction density and electrical conductivity of the lithium manganese iron phosphate positive electrode material.

[0022] Preferably, the temperature of the feed inlet of the spray drying in step (2) is 160-240°C, for example, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the temperature at the discharge port of the spray drying in step (2) is 80-140°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or 140°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the three-stage sintering includes sequentially performing a first stage sintering, a second stage sintering and a third stage sintering.

[0025] Preferably, the heating rates of the first sintering stage, the second sintering stage and the third sintering stage are independently 1 to 10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the sintering temperature of the first stage sintering is 120-350°C, for example, 120°C, 125°C, 150°C, 17°C5, 200°C, 225°C, 250°C, 275°C, 300°C, 325°C or 350°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the sintering time of the first stage sintering is 1 to 6 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] Preferably, the sintering temperature of the second stage sintering is 550-650°C, for example, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640 or 650, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Preferably, the sintering time of the second sintering stage is 1 to 10 hours, for example 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the sintering temperature of the third stage sintering is 780-830°C, for example, 780°C, 790°C, 800°C, 810°C, 820°C or 830°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the sintering time of the third stage sintering is 0.5 to 3 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] The three-stage sintering provided by the present invention adopts three-stage temperature-increasing sintering, which is more conducive to improving the compaction density and conductivity of the lithium iron manganese phosphate positive electrode material.

[0033] Preferably, the product after the three-stage sintering is pulverized.

[0034] In the present invention, the pulverization process is a conventional technical solution, and those skilled in the art can make adaptive adjustments according to actual needs. For example, the present invention provides a pulverization process method:

[0035] In an environment with humidity <50%, the crushing process is performed at a crushing pressure of 600-800 kPa, for example 600 kPa, 650 kPa, 700 kPa, 750 kPa or 800 kPa, but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] As a preferred technical solution, the preparation method comprises the following steps:

[0037] (1) sand milling the first slurry at a rotation speed of 1500 to 3000 rpm to obtain a second slurry, wherein the D50 of the solid particles in the second slurry is 120 to 150 nm;

[0038] (2) spray drying the second slurry, sintering the spray-dried product at 120-350° C. for 1-6 h in the first stage, then heating to 550-650° C. for 1-10 h in the second stage, and further heating to 780-830° C. for 0.5-3 h in the third stage to obtain the lithium manganese iron phosphate positive electrode material;

[0039] The first slurry includes a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source and a solvent.

[0040] It should be noted that, in the preparation method provided by the present invention, the specific types of substances used in the preparation of raw materials and the specific addition ratios of the raw materials used in the preparation are conventional technical solutions, and those skilled in the art can adaptively select and adjust them according to actual needs.

[0041] Specifically, in the present invention, the addition amounts of the lithium source, manganese source, iron source, and phosphorus source are adjusted according to the chemical general formula of LiMn 1-x Fe x PO4, where 0 < x ≤ 1, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1, but not limited to the listed values, and other unlisted values within the numerical range are equally applicable. Preferably, 0 < x ≤ 0.5;

[0042] Optionally, the lithium source includes but is not limited to at least one of lithium carbonate, lithium hydroxide, lithium oxalate, or lithium nitrate;

[0043] Optionally, the valence of manganese in the manganese source can be +2 or +3, as long as the reaction is not affected. For example, it includes but is not limited to at least one of manganese sulfate, manganese(III) oxide, manganese(II) chloride, manganese(II) bromide, manganese(II) nitrate, manganese(II) perchlorate, manganese(II) sulfate, and manganese(II) acetate;

[0044] Optionally, the valence of iron in the iron source can be +2 or +3, as long as the reaction is not affected. For example, it includes but is not limited to at least one of iron(III) oxide, iron(II) chloride, iron(II) bromide, iron(II) fluorosilicate, iron(II) nitrate, iron(II) perchlorate, iron(II) sulfate, and iron(II) acetate;

[0045] In the present invention, here it can be changed to when the manganese source and iron source are in a high valence state, a reducing agent can be additionally added during the reaction process; a reducing agent can be added during the reaction process to prevent substances from being oxidized, such as ascorbic acid can be added;

[0046] Optionally, the phosphorus source includes but is not limited to at least one of phosphoric acid, ammonium phosphate, ammonium dihydrogen phosphate, or diammonium hydrogen phosphate;

[0047] Optionally, the solvent includes water.

[0048] In a second aspect, the present invention provides a lithium iron manganese phosphate cathode material, which is prepared by the preparation method as described in the first aspect.

[0049] In a third aspect, the present invention further provides a lithium-ion battery, which includes the lithium iron manganese phosphate cathode material as described in the second aspect.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] The preparation method provided by the present invention cooperates with sand milling, spray drying and three-stage sintering, grinds the precursor D50 to an ultra-small particle size by sand milling, and undergoes subsequent spray drying and three-stage sintering, thereby greatly reducing the internal resistance of the material and improving the electrical conductivity of the material. At the same time, the uniform distribution of elements in the precursor material is achieved, and the compaction density of the lithium iron manganese phosphate positive electrode material is improved, so that the lithium iron manganese phosphate positive electrode material with a wide distribution of large and small particles, high electrical conductivity and high compaction density is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a graph showing the test results of the electronic conductivity of the lithium iron manganese phosphate positive electrode material provided in Example 1. DETAILED DESCRIPTION

[0053] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0055] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0056] Example 1

[0057] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:

[0058] (1) dispersing lithium carbonate, manganese trioxide, iron trioxide, ammonium phosphate, and tannic acid in water to obtain a first slurry, wherein Li:Mn:Fe:P=1.02:0.6:0.4:1, and based on the total mass of lithium carbonate, manganese trioxide, iron trioxide, and ammonium phosphate being 100wt%, the amount of tannic acid added is 1.5wt%, and a first slurry with a solid content of 35% is obtained;

[0059] (2) grinding the first slurry obtained in step (1) to D50 = 150 nm by sand milling, wherein the speed of the sand mill is 2300 rpm, to obtain a uniformly dispersed second slurry;

[0060] (3) spray drying and granulating the second slurry obtained in step (2) to obtain a solid mixture, wherein the feed inlet temperature is 230° C. and the discharge outlet temperature is 95° C.;

[0061] (4) The solid mixture obtained in step (3) is placed in a graphite sagger and compacted, and then the sagger containing the solid mixture is placed in an atmosphere furnace for calcination, wherein the first stage of sintering is: the room temperature is 25°C, the temperature is increased by 5°C / min to 320°C and kept at this temperature for 2 hours; the second stage of sintering is: the temperature is increased by 2°C / min to 610°C / min and kept at this temperature for 5 hours; the third stage of sintering is: the temperature is increased by 10°C / min to 800°C and kept at this temperature for 1 hour, to obtain a sintered material;

[0062] (5) The sintered material obtained in step (4) is crushed by air flow to D50 = 1.2 μm, Span ≥ 1.8 (Span = (D90-D10) / D50), wherein the air flow crushing pressure is 700 kPa, so as to obtain the lithium manganese iron phosphate positive electrode material, and the surface of the material is coated with carbon material, and the inside of the material is also distributed with carbon material. The chemical formula of the obtained positive electrode material is LiMn 0.6 Fe 0.4 PO4 / C.

[0063] Example 2

[0064] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:

[0065] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:

[0066] (1) dispersing lithium carbonate, manganese trioxide, iron trioxide, ammonium phosphate, and tannic acid in water to obtain a first slurry, wherein Li:Mn:Fe:P=1.02:0.6:0.4:1, and based on the total mass of lithium carbonate, manganese trioxide, iron trioxide, and ammonium phosphate being 100wt%, the amount of tannic acid added is 2wt%, and a first slurry with a solid content of 20% is obtained;

[0067] (2) grinding the first slurry obtained in step (1) to D50 = 120 nm by sand milling, wherein the speed of the sand mill is 1500 rpm, to obtain a uniformly dispersed second slurry;

[0068] (3) spray drying and granulating the second slurry obtained in step (2) to obtain a solid mixture, wherein the feed inlet temperature is 160° C. and the discharge outlet temperature is 80° C.;

[0069] (4) The solid mixture obtained in step (3) is placed in a graphite sagger and compacted, and then the sagger containing the solid mixture is placed in an atmosphere furnace for calcination, wherein the first stage of sintering is: the room temperature is 25°C, the temperature is increased at 3°C / min to 130°C and kept at this temperature for 6 hours; the second stage of sintering is: the temperature is increased at 5°C / min to 550°C / min and kept at this temperature for 10 hours; the third stage of sintering is: the temperature is increased at 5°C / min to 780°C and kept at this temperature for 3 hours, to obtain a sintered material;

[0070] (5) The sintered material obtained in step (4) is crushed by air flow to D50 = 1.2 μm, Span ≥ 1.8 (Span = (D90-D10) / D50), wherein the air flow crushing pressure is 600 kPa, so as to obtain the lithium manganese iron phosphate positive electrode material, and the surface of the material is coated with carbon material, and the inside of the material is also distributed with carbon material. The chemical formula of the obtained positive electrode material is LiMn 0.6 Fe 0.4 PO4 / C.

[0071] Example 3

[0072] This embodiment provides a method for preparing a lithium manganese iron phosphate positive electrode material, the preparation method comprising the following steps:

[0073] (1) dispersing lithium carbonate, manganese trioxide, iron trioxide, ammonium phosphate, and tannic acid in water to obtain a first slurry, wherein Li:Mn:Fe:P=1.02:0.6:0.4:1, and based on the total mass of lithium carbonate, manganese trioxide, iron trioxide, and ammonium phosphate being 100wt%, the amount of tannic acid added is 3wt%, and a first slurry with a solid content of 45% is obtained;

[0074] (2) grinding the first slurry obtained in step (1) to D50 = 135 nm by sand milling, wherein the speed of the sand mill is 3000 rpm, to obtain a uniformly dispersed second slurry;

[0075] (3) spray drying and granulating the second slurry obtained in step (2) to obtain a solid mixture, wherein the feed inlet temperature is 200° C. and the discharge outlet temperature is 100° C.;

[0076] (4) The solid mixture obtained in step (3) is placed in a graphite sagger and compacted, and then the sagger containing the solid mixture is placed in an atmosphere furnace for calcination, and the first stage sintering, the second stage sintering and the third stage sintering are performed in sequence. The first stage sintering: the room temperature is 25°C, and the temperature is increased by 5°C / min to 350°C and kept for 1 hour; the second stage sintering: the temperature is increased by 2°C / min to 650°C / min and kept for 1 hour; the third stage sintering: the temperature is increased by 10°C / min to 830°C and kept for 0.5 hour to obtain a sintered material;

[0077] (5) The sintered material obtained in step (4) is crushed by air flow to D50 = 1.2 μm, Span ≥ 1.8 (Span = (D90-D10) / D50), wherein the air flow crushing pressure is 700 kPa, so as to obtain the lithium manganese iron phosphate positive electrode material, and the surface of the material is coated with carbon material, and the inside of the material is also distributed with carbon material. The chemical formula of the obtained positive electrode material is LiMn 0.6 Fe 0.4 PO4 / C.

[0078] Example 4

[0079] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the material is ground to D50=300 nm by sand grinding.

[0080] The rest of the preparation methods and parameters were the same as those in Example 1.

[0081] Example 5

[0082] The difference between this embodiment and embodiment 1 is that the rotation speed of the sand mill in step (2) of this embodiment is 1000 rpm.

[0083] The rest of the preparation methods and parameters were the same as those in Example 1.

[0084] Example 6

[0085] The difference between this embodiment and embodiment 1 is that in step (4) of this embodiment, the sintering temperature of the first stage sintering is 450°C.

[0086] The rest of the preparation methods and parameters were the same as those in Example 1.

[0087] Example 7

[0088] The difference between this embodiment and embodiment 1 is that in step (4) of this embodiment, the sintering temperature of the second stage sintering is 500°C.

[0089] The rest of the preparation methods and parameters were the same as those in Example 1.

[0090] Example 8

[0091] The difference between this embodiment and embodiment 1 is that in step (4) of this embodiment, the sintering temperature of the third stage sintering is 900°C.

[0092] The rest of the preparation methods and parameters were the same as those in Example 1.

[0093] Comparative Example 1

[0094] The difference between this comparative example and Example 1 is that in this comparative example, no sand milling treatment is performed, and the first slurry is directly spray-dried.

[0095] The rest of the preparation methods and parameters were the same as those in Example 1.

[0096] Comparative Example 2

[0097] The difference between this comparative example and Example 1 is that this comparative example adopts oven drying method instead of spray drying, that is, the second slurry after sand milling is oven dried.

[0098] The rest of the preparation methods and parameters were the same as those in Example 1.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 1 is that in step (4) of this comparative example, the temperature is directly increased to 800° C. at a heating rate of 10° C. / min and kept for 1 h to obtain the sintered material, that is, neither the first stage sintering nor the second stage sintering is performed.

[0101] The rest of the preparation methods and parameters were the same as those in Example 1.

[0102] Comparative Example 4

[0103] The difference between this comparative example and Example 1 is that in step (4) of this comparative example, the first stage sintering is not performed, and the second stage sintering and the third stage sintering are directly performed.

[0104] The rest of the preparation methods and parameters were the same as those in Example 1.

[0105] Comparative Example 5

[0106] The difference between this comparative example and Example 1 is that in step (4) of this comparative example, the second stage sintering is not performed, and only the first stage sintering and the third stage sintering are performed.

[0107] The rest of the preparation methods and parameters were the same as those in Example 1.

[0108] The compaction density and electrical conductivity of the lithium iron manganese phosphate positive electrode materials provided in Examples 1-8 and Comparative Examples 1-5 were tested:

[0109] Compacted density: Weigh 1g of the sample to be tested, fill it into the groove of the compacted density meter, apply 3T pressure, maintain the pressure for 30s, and record the powder compacted density of the material at 3T;

[0110] Conductivity: The four-probe method was used to perform a powder impedance test on the lithium manganese iron phosphate positive electrode active materials prepared in the above embodiments and comparative examples at 25°C.

[0111] Figure 1 The test result diagram of the electronic conductivity of the lithium manganese iron phosphate positive electrode material provided in Example 1 is shown. Figure 1It can be seen that the electronic conductivity of the modified lithium manganese iron phosphate after sand grinding, spray drying, three-stage calcination and carbon coating with tannic acid as the carbon source is increased from 10 -13 S / cm increased to 81.3mS / cm, and the compaction density reached 2.61g / cm 3 .

[0112] The test results of the above tests are shown in Table 1.

[0113] Table 1

[0114]

[0115]

[0116] Lithium-ion batteries were prepared using the lithium iron manganese phosphate positive electrode materials provided in Examples 1-8 and Comparative Examples 1-5, respectively.

[0117] (1) Preparation of positive electrode sheet

[0118] Weigh 0.3000g of polyvinylidene fluoride binder (PVDF) in 10.8g of N-methylpyrrolidone (NMP), stir and completely dissolve; then add 2.4000g of lithium iron manganese phosphate positive electrode material (from Examples 1 to 8 and Comparative Examples 1 to 5, respectively) and 0.3000g of carbon black conductive agent (SP), stir evenly to obtain a paste; wherein, the mass ratio of lithium iron manganese phosphate-carbon composite material, polyvinylidene fluoride binder (PVDF), and carbon black conductive agent (SP) is 8:1:1; use an applicator to evenly coat the paste on aluminum foil, and then put it into a blast drying oven and dry it at a temperature of 60°C for 3.0h. After drying, transfer it to a vacuum drying oven and vacuum dry it at a temperature of 120°C for 6.0h. The dried positive electrode sheet is rolled and punched to obtain a disc with a diameter of 16.0mm as a positive electrode sample pole sheet. In addition, roll and punch four uncoated blank aluminum foil discs for standby use.

[0119] (2) Assembly of CR2032 button battery

[0120] The prepared positive electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the PE-PP composite film was used as the battery separator, and 1.0 mol / L LiPF6 / (DMC+DMC) was used as the electrolyte, wherein the volume ratio of EC to DMC was 1:1, and a CR2032 button battery was assembled;

[0121] (3) Performance test:

[0122] The charge and discharge voltage is 2.0V~4.3V. The button battery is subjected to cycle charge and discharge tests at charge and discharge rates of 0.1C, 0.5C and 1.0C. The test results are shown in Table 2.

[0123] Table 2

[0124]

[0125] In summary, the preparation method provided by the present invention, through the coordinated cooperation of sand milling, spray drying and three-stage sintering, grinds the precursor D50 to an ultra-small particle size by sand milling, and after subsequent spray drying and three-stage sintering, greatly reduces the internal resistance of the material, improves the electrical conductivity of the material, and at the same time achieves a uniform distribution of elements in the precursor material, improves the compaction density of the lithium iron manganese phosphate positive electrode material, and obtains a lithium iron manganese phosphate positive electrode material with a wide distribution of particle sizes, high conductivity and high compaction density.

[0126] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The preparation method comprises the following steps: (1) sand-milling the first slurry to obtain a second slurry; (2) spray drying the second slurry and performing three-stage sintering to obtain the lithium manganese iron phosphate positive electrode material; The first slurry includes a lithium source, a manganese source, an iron source, a phosphorus source and a solvent.

2. The preparation method according to claim 1, characterized in that: The solid content of the first slurry is 20-45%; Preferably, the first slurry also includes a carbon source.

3. The preparation method according to claim 1 or 2, characterized in that: The rotation speed of the sand grinding treatment in step (1) is 1500 to 3000 rpm; Preferably, the D50 of the solid particles in the second slurry is 120 to 300 nm, preferably 120 to 150 nm.

4. The preparation method according to any one of claims 1 to 3, characterized in that The temperature of the feed port of the spray drying in step (2) is 160-240° C. Preferably, the temperature of the discharge port of the spray drying in step (2) is 80-140°C.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The three-stage sintering includes sequentially performing a first stage sintering, a second stage sintering and a third stage sintering.

6. The preparation method according to claim 5, characterized in that: The heating rates of the first sintering stage, the second sintering stage and the third sintering stage are independently 1 to 10°C / min; Preferably, the sintering temperature of the first stage sintering is 120-350° C., and the sintering time of the first stage sintering is 1-6 hours; Preferably, the sintering temperature of the second stage sintering is 550-650°C, and the sintering time of the second stage sintering is 1-10h; Preferably, the sintering temperature of the third stage sintering is 780-830° C., and the sintering time of the third stage sintering is 0.5-3 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The product after the three-stage sintering is pulverized.

8. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) sand milling the first slurry at a rotation speed of 1500 to 3000 rpm to obtain a second slurry, wherein the D50 of the solid particles in the second slurry is 120 to 150 nm; (2) spray drying the second slurry, sintering the spray-dried product at 120-350° C. for 1-6 h in the first stage, then heating to 550-650° C. for 1-10 h in the second stage, and further heating to 780-830° C. for 0.5-3 h in the third stage to obtain the lithium manganese iron phosphate positive electrode material; The first slurry includes a lithium source, a manganese source, an iron source, a phosphorus source, a carbon source and a solvent.

9. A lithium manganese iron phosphate positive electrode material, characterized in that: The lithium manganese iron phosphate positive electrode material is prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium iron manganese phosphate positive electrode material as claimed in claim 9.

Citation Information

Patent Citations

  • Iron manganese vanadium phosphate precursor, iron manganese vanadium lithium phosphate / carbon anode material and preparation method

    CN106486668A

  • Method for preparing manganese phosphate iron phosphate-carbon composite material and manganese phosphate iron phosphate-carbon composite material

    CN110323434A

  • Multi-element composite phosphate nanometer anode material and preparation method thereof

    CN104934600A

  • A lithium iron phosphate with high compact density and a preparation method thereof

    CN109192948A

  • Manufacturing method, apparatus and system for positive electrode material

    WO2023051502A1

Cited By

  • Lithium manganese iron phosphate grain composition method based on high and low temperature pre-sintering and positive electrode slurry thereof

    CN121849898A

  • Preparation method for lithium manganese iron phosphate positive electrode material, positive electrode material, and lithium-ion battery

    WO2026081418A1